Ultrahigh Conductive Copper/Large Flake Size Graphene Heterostructure Thin‐Film with Remarkable Electromagnetic Interference Shielding Effectiveness. Issue 20 (17th April 2018) - Wang, Zhe; Mao, Boyang; Wang, Qianlong; Yu, Jun; Dai, Jixiang; Song, Rongguo; Pu, Zonghua; He, Daping; Wu, Zhi; Mu, Shichun
Abstract: To guarantee the normal operation of next generation portable electronics and wearable devices, together with avoiding electromagnetic wave pollution, it is urgent to find a material possessing flexibility, ultrahigh conductive, and superb electromagnetic interference shielding effectiveness (EMI SE) simultaneously. In this work, inspired by a building bricks toy with the interlock system, we design and fabricate a copper/large flake size graphene (Cu/LG) composite thin film (≈8.8 μm) in the light of high temperature annealing of a large flake size graphene oxide film followed by magnetron sputtering of copper. The obtained Cu/LG thin‐film shows ultrahigh thermal conductivity of over 1932.73 (±63.07) W m −1 K −1 and excellent electrical conductivity of 5.88 (±0.29) × 10 6 S m −1 . Significantly, it also exhibits a remarkably high EMI SE of over 52 dB at the frequency of 1–18 GHz. The largest EMI SE value of 63.29 dB, accorded at 1 GHz, is enough to obstruct and absorb 99.99995% of incident radiation. To the best of knowledge, this is the highest EMI SE performance reported so far in such thin thickness of graphene‐based materials. These outstanding properties make Cu/LG film a promising alternative building block for power electronics, microprocessors, and flexible electronics. Abstract : Cu/large flake size graphene heterostructure thin films fabricated by magnetron sputtering not only exhibit an excellent combination of ultrahigh in‐plane thermal and electrical conductivity, but also display remarkable electromagnetic interface shielding. This new film and its fabrication method can arouse the interests of all related working in both academic and industrial research.